2000
DOI: 10.1161/01.res.87.11.1063
|View full text |Cite
|
Sign up to set email alerts
|

Gene Therapy for Attenuating Cardiac Allograft Arteriopathy Using Ex Vivo E2F Decoy Transfection by HVJ-AVE–Liposome Method in Mice and Nonhuman Primates

Abstract: Abstract-Cardiac allograft arteriopathy, which limits the long-term survival of recipients, is characterized by diffuse intimal thickening composed of proliferative smooth muscle cells. The transcription factor E2F plays a pivotal role in the coordinated transcription of cell-cycle regulatory genes. To test the hypothesis that double-stranded DNA with specific affinity for E2F (E2F decoy) is effective in preventing intimal hyperplasia, we performed ex vivo single intraluminal delivery of E2F decoy into cardiac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(29 citation statements)
references
References 44 publications
0
29
0
Order By: Relevance
“…34 Decoy technology has been proposed as a novel therapeutic tool for use in molecular medicine for treating several disorders. 29,[34][35][36] We previously demonstrated that E2F and the AP-1 ring-type decoy ODN efficiently inhibited the expression of specific genes in vivo, and that the E2F decoy ODN effectively inhibited the growth of human tumor cells and cell proliferation in mesangial cells. 37,38 The Sp1 decoy prevents tumor necrosis factor (TNF)-a from inducing VEGF, TGF-b1, and tissue factor in cancer cells, and inhibits COL1A2 promoter activity in cultured fibroblast and in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…34 Decoy technology has been proposed as a novel therapeutic tool for use in molecular medicine for treating several disorders. 29,[34][35][36] We previously demonstrated that E2F and the AP-1 ring-type decoy ODN efficiently inhibited the expression of specific genes in vivo, and that the E2F decoy ODN effectively inhibited the growth of human tumor cells and cell proliferation in mesangial cells. 37,38 The Sp1 decoy prevents tumor necrosis factor (TNF)-a from inducing VEGF, TGF-b1, and tissue factor in cancer cells, and inhibits COL1A2 promoter activity in cultured fibroblast and in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…In vitro transfection of cis elements that decoy against nuclear factors leads to alteration of gene expression and was recently proposed in molecular medicine as a novel tool for the possible therapy of several disorders (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12). One of the most effective decoy approaches so far described involves nuclear proteins belonging to the NF-B 1 superfamily (7)(8)(9)(13)(14)(15)(16)(17)(18)(19)(20).…”
mentioning
confidence: 99%
“…The transcription factor E2F regulates multiple cell-cycle regulatory genes, which are critical to the process of cell growth and proliferation. 70 To clarify the effects of E2F decoy ODN on CAV, we used both murine and monkey cardiac transplant models, which showed that E2F decoy ODN transfer into the allografts specifically abolishes E2F activity and inhibites CAV 71 (Figure 3). Another critical transcription factor, nuclear factor-κB (NF-κB), plays a pivotal role in the coordinated transcription of multiple inflammatory genes.…”
Section: Treatments Under Investigationmentioning
confidence: 99%